(untitled) (Materiali di Estetica. Terza serie, 2020)
A lost and rediscovered drawing by Leonardo da Vinci, what does it inspire? What circumstantial investments does it imply to be recognized? In a nutshell, this is the dispute: the recovery and identification of a graphic artifact referable in the first instance to Leonardo’s school, and, in the second instance to Leonardo da Vinci himself.